The need for intentional communication and design in environmental citizen science - Lin Hunter, Danielle Elizabeth Yut Yun, author; Balgopal, Meena M., advisor; Newman, Gregory J., committee member; Champ, Joseph G., committee member; von Fischer, Joe C., committee member (Colorado State University. Libraries, 2022)
Citizen science projects involve members of the public in the process of science. These joint efforts between scientists and the public have benefited scientific understanding, especially in fields like ecology and environmental science that investigate broad geographic and temporal scale phenomena, as well as social benefits like increases in scientific literacy for volunteers. While citizens have contributed to our scientific understanding of the natural world for centuries, researchers have only been conducting studies on citizen science processes and outcomes for the past couple of decades. As the field of citizen science research is relatively new, there is a need to better understand the communication, structures, and practices of the discipline. The studies in this dissertation focus on various aspects of communication in the field of citizen science. Chapter 2 describes a content analysis of citizen science project descriptions on CitSci.org and hyperlinked websites to better understand how project leaders describe volunteer tasks and project benefits. Specifically, we were interested in the links between different types of engagement in citizen science and learning outcomes. Citizen science projects often struggle to retain volunteers, so understanding how volunteer tasks align with their motives for participation is informative. We conducted a content analysis of CitSci.org project descriptions (n = 152) along with project descriptions found on hyperlinked websites (n = 23), analyzing volunteer tasks according to cognitive order as defined by Bloom's Taxonomy, an educational framework designed to classify an individual's depth of knowledge. We also considered who benefits from the tasks that volunteers performed. We found that most projects described volunteers as performing (low order) tasks and described the benefits to citizen science projects. Our analysis indicates that project managers described the scientific process in a limited capacity, which has implications for volunteer scientific literacy. We concluded that when volunteers have a limited role in the project and described benefits misaligned with volunteer motives for participation, they are better described as citizen technicians than citizen scientists. In the third chapter, we examined how members of the citizen science community perceive various terms used to brand citizen science. While citizen science projects engage the public in science, they often struggle to recruit diverse participants. Citizen science project leaders are increasingly trying to promote inclusivity by rebranding as "community science" to avoid the term "citizen." We argue that rebranding efforts, while well-intentioned, are uninformed by research. To address this knowledge gap, we distributed a survey to those who participate in citizen and community science (n = 180). We found differences in how well known and accepted the terms are, who is perceived as initiating and benefiting from the projects, and associated levels of inclusivity. Our findings suggest that projects seeking to increase and diversify their volunteer participation should consider what branding they use. Chapter 4 describes the experiences of citizen science project leaders as they balance multiple project goals. Project leaders often have to manage different goals and the competing interests of scientists, volunteers, funding agencies, and community partners. These challenges can diminish project leaders' capacities to effectively fulfill their roles. We interviewed citizen science project leaders (n = 65) to better understand their perceptions of barriers and opportunities in meeting goals. We found that project leaders who perceived misalignment between their own goals for citizen science projects and what they perceived to be their organization's goals more frequently reported challenges related to balancing various project interests, convincing colleagues of data trustworthiness and quality, and being part-time staff. We describe important implications for how organizations engaging in citizen science can address these challenges and better achieve goals. These studies examine communication in citizen science from three vantage points: 1) how volunteer tasks and project benefits are described, 2) how citizen science projects are branded, and 3) how organizations communicate about the goals of their projects. The findings address knowledge gaps in citizen science research related to how people communicate and by documenting the perspectives of those who lead projects.
Keywords: community science; informal science education; science communication; inclusion; citizen science; public engagement in science